2020
DOI: 10.1007/s10344-020-01403-z
|View full text |Cite
|
Sign up to set email alerts
|

Survival rates on pre-weaning European hares (Lepus europaeus) in an intensively used agricultural area

Abstract: The primary cause of the long-term decline in European hares’ (Lepus europaeus) population throughout Europe is widely assumed to be the intensification of agriculture. A critical component in this population dynamics is seen in the survival of leverets from birth to reproductive age. In European hares, the first stage of life until weaning has been sparsely studied, in particular habitat selection, movements and survival rate, as juveniles’ precocial lifestyle is dominated by any kind of anti-predation behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…In general, European hares benefit from increased habitat heterogeneity, i.e. a small-scale mosaic of suitable habitats for foraging and cover with high proportions of edge-zones [36,[38][39][40][41][42]. Measures aimed at increasing the structural diversity of SRC, for example harvesting in sections in order to develop a mosaic of different age-classes, or integrating accompanying structures such as clearings, rides or wide headlands, could therefore improve the habitat quality of SRC for the European hare and also for other mammal species.…”
Section: Discussionmentioning
confidence: 99%
“…In general, European hares benefit from increased habitat heterogeneity, i.e. a small-scale mosaic of suitable habitats for foraging and cover with high proportions of edge-zones [36,[38][39][40][41][42]. Measures aimed at increasing the structural diversity of SRC, for example harvesting in sections in order to develop a mosaic of different age-classes, or integrating accompanying structures such as clearings, rides or wide headlands, could therefore improve the habitat quality of SRC for the European hare and also for other mammal species.…”
Section: Discussionmentioning
confidence: 99%
“…There is a high mortality rate in young hares in the wild in the first weeks of life, previous studies reported leveret mortality ranging from 65% [ 9 ] to 84% [ 11 ] in the first month. Thus, it is particularly important to limit the factors that further contribute to their mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Although hares develop a large number of survival strategies [ 8 ], their mortality rate is extremely high, particularly among young in the first two weeks of life [ 9 ]. Hansen [ 10 ] reported a mortality rate of as much as 80% in leverets as a result of a shortage of suitable habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Survival rates in adult individuals were higher than in young ones regardless of sex (Φ = 0,507). The survival rate of radiolabelled brown hares after the first month was 0,35 in Voigt and Siebert (2020). Half of the deaths occurred in the first 13 days.…”
Section: Survival Patternmentioning
confidence: 96%